2010
DOI: 10.1002/cbf.1630
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent plasticity of stem cells and liver repopulation

Abstract: Different types of stem cells have a role in liver regeneration or fibrous repair during and after several liver diseases. Otherwise, the origin of hepatic and/or extra-hepatic stem cells in reactive liver repopulation is under controversy. The ability of the human body to self-repair and replace the cells and tissues of some organs is often evident. It has been estimated that complete renewal of liver tissue takes place in about a year. Replacement of lost liver tissues is accomplished by proliferation of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 98 publications
0
10
0
1
Order By: Relevance
“…Oval cells are the hepatic progenitor cells and express markers of hepatic origin (Gennero et al, ). BMSCs after 14 days of preconditioning with growth factors started expressing oval cells‐specific markers as evidenced by immunocytochemical analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oval cells are the hepatic progenitor cells and express markers of hepatic origin (Gennero et al, ). BMSCs after 14 days of preconditioning with growth factors started expressing oval cells‐specific markers as evidenced by immunocytochemical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…OCs are bipotent and are able to give rise to both cholangiocytes and hepatocytes. These cells co‐express biliary and hepatocyte markers such as cytokeratin‐19 (CK19), AFP, and ALB and also mesenchymal stem cell (MSC) markers; c‐kit and Thy‐1 (CD90) (Gennero et al, ; Jackson et al, ). Oval cells are there in limited number in normal adult liver so their isolation is not a practical therapeutic option in human liver diseases (Schmelzer et al, ; Bird et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent rapid developments in stem cell biology have made its use possible in the treatment of several types of diseases 25,26 . In this context, adult stem cells have shown the capacity for regeneration of damaged tissues or organs, including the liver 27,28 . Studies have demonstrated that bone marrow‐derived MSC migrate into the damaged liver and contribute to overcoming liver dysfunction 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…are not yet fully understood [84,85]. Given the multifunctional role assigned to BMP signaling during early liver development, including hepatic specification and liver morphogenesis, a potential role for BMP in oval cell activation, expansion and differentiation should be considered.…”
Section: Role Of Bmps In Liver Developmentmentioning
confidence: 99%